Exploring The Impact Of Digital Accounting And Digital Zakat On Improving Business Sustainability In The Middle East And Malaysia - Attallah Hassan Mohamed Al-Taani; Murad Ali Ahmad Al-Zaqeba; Hussein Mousa Ahmad Maabreh; Baker Akram Falah Jarah (Institute of Advanced Science Extension (IASE), 2024)
Indexed by WOS/ Scopus